Ice and firn heterogeneity within Larsen C Ice Shelf from borehole optical televiewing. Issue 5 (20th May 2017) - Ashmore, David W.; Hubbard, Bryn; Luckman, Adrian; Kulessa, Bernd; Bevan, Suzanne; Booth, Adam; Munneke, Peter Kuipers; O'Leary, Martin; Sevestre, Heidi; Holland, Paul R.
Abstract: We use borehole optical televiewing (OPTV) to explore the internal structure of Larsen C Ice Shelf (LCIS). We report a suite of five 90 m long OPTV logs, recording a light‐emitting diode‐illuminated, geometrically correct image of the borehole wall, from the northern and central sectors of LCIS collected during austral spring 2014 and 2015. We use a thresholding‐based technique to estimate the refrozen ice content of the ice column and exploit a recently calibrated density‐luminosity relationship to reveal its structure. All sites are dense and strongly influenced by surface melt, with frequent refrozen ice layers and mean densities, between the depths of 1.87 and 90 m, ranging from 862 to 894 kg m −3 . We define four distinct units that comprise LCIS and relate these to ice provenance, dynamic history, and past melt events. These units are in situ meteoric ice with infiltration ice (U1), meteoric ice which has undergone enhanced densification (U2), thick refrozen ice (U3), and advected continental ice (U4). We show that the OPTV‐derived pattern of firn air content is consistent with previous estimates, but that a significant proportion of firn air is contained within U4, which we interpret to have been deposited inland of the grounding line. The structure of LCIS is strongly influenced by the E‐W gradient in föhn‐driven melting, with sites close to the Antarctic Peninsula being predominantly composed of refrozen ice. Melting is also substantial toward the ice shelf center with >40% of the overall imaged ice column being composed of refrozen ice. Key Points: Larsen C Ice Shelf is composed of distinct material units recording its dynamic and melt history Existing firn air model estimates commonly neglect the presence of buried low‐density continental ice >40% of the firn zone of Larsen C is composed of refrozen ice in its central and northern sectors